ANALISIS DAYA DUKUNG DAN PENURUNAN TIANG PANCANG TERHADAP HASIL PDA PADA PROYEK SPAM PEKANBARU-BANGKINANG - Arifin, Arifin; Yusa, Muhamad; Wibisono, Gunawan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The drinking water supply system (SPAM) is an infrastructure facility specifically designed to provide clean and safe drinking water that meets established health standards. In this project, the construction buildings utilize foundations in the form of piles and bored piles, which serve as essential structural elements to support and distribute loads from the columns to the underlying hard soil layer. A properly designed foundation ensures the stability and durability of the overall structure. This study aims to analyze and determine the bearing capacity of the foundation using several analytical approaches, namely the Meyerhoff, Reese & Wright, and Luciano Decourt methods, while the settlement analysis is carried out using the Fellenius and Vesic methods. The research was conducted in Kampar Regency, Riau Province, Indonesia. The data used in this analysis include Standard Penetration Test (SPT) data and Pile Driving Analyzer (PDA) test results obtained from field observations. The calculation results indicate that the bearing capacity obtained from the Meyerhoff method is 103 tons, Reese & Wright 176 tons, Luciano Decourt 353 tons, and PDA 204 tons. Meanwhile, the settlement results show values of 10.7 mm for the Fellenius method, 16.05 mm for the Vesic method, and 14.5 mm for PDA measurements.